Penerapan Arsitektur Bioklimatik Ken Yeang pada Perancangan Asrama Mahasiswa di Kecamatan Percut Sei Tuan - Defa Hardianta Perasi; Neneng Yulia Barky (Universitas Medan Area, 2026)
This study aims to apply Ken Yeang’s bioclimatic architectural approach to the design of a student dormitory in Percut Sei Tuan District, Deli Serdang Regency, as a response to the increasing demand for student housing and the tropical humid climate conditions. The research employs a qualitative method with a descriptive-analytical approach and architectural design, conducted through site analysis including climate conditions, solar orientation, wind direction, and surrounding environment. Ken Yeang’s bioclimatic principles are implemented through north–south building orientation, placement of building cores on the east and west sides, optimization of cross ventilation, utilization of natural lighting, application of passive shading devices, green balconies, and integration of transitional spaces and landscape elements. The design outcome results in a four-story student dormitory with a capacity of approximately 300 occupants, divided into male and female dormitories. The application of bioclimatic principles enhances thermal comfort, improves energy efficiency, and creates a healthy, functional, and sustainable student housing environment suitable for tropical regions.